2024
DOI: 10.1089/mab.2023.0033
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Novel Cancer-Specific Anti-HER2 Monoclonal Antibody H2Mab-250/H2CasMab-2 for Breast Cancers

Mika K. Kaneko,
Hiroyuki Suzuki,
Yukinari Kato

Abstract: Overexpression of human epidermal growth factor receptor 2 (HER2) in breast and gastric cancers is an important target for monoclonal antibody (mAb) therapy. All therapeutic mAbs, including anti-HER2 mAbs, exhibit adverse effects probably due to the recognition of antigens expressed in normal cells. Therefore, tumor-selective or specific mAbs can be beneficial in reducing the adverse effects. In this study, we established a novel cancer-specific anti-HER2 antibody, named H2Mab-250/H2CasMab-2 (IgG1, kappa). H2M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…We have developed cancer-specific mAbs (CasMabs) against HER2 (H2Mab-214 and H2Mab-250) [34,35], podocalyxin (PcMab-6 and PcMab-60) [36,37], and podoplanin (LpMab-2 and LpMab-23) [38,39] and revealed that these mAbs react with cancer cells, but not normal cells in flow cytometry. The strategy used in this study is also applicable to select anti-EphB2 CasMabs from Eb2Mabs (Supplementary Table S1) or clones from remaining positive wells.…”
Section: Discussionmentioning
confidence: 99%
“…We have developed cancer-specific mAbs (CasMabs) against HER2 (H2Mab-214 and H2Mab-250) [34,35], podocalyxin (PcMab-6 and PcMab-60) [36,37], and podoplanin (LpMab-2 and LpMab-23) [38,39] and revealed that these mAbs react with cancer cells, but not normal cells in flow cytometry. The strategy used in this study is also applicable to select anti-EphB2 CasMabs from Eb2Mabs (Supplementary Table S1) or clones from remaining positive wells.…”
Section: Discussionmentioning
confidence: 99%